Tubular flange plate girders with corner square web openings in the panel of maximum shear: Strength and behaviour. (February 2016) - El-Khoriby, S.R.; Hassanein, M.F.; Kharoob, O.F.; El Hadidy, A.M.; Alnaggar, G.A.N.
Abstract: Eccentric web openings are usually unavoidable in the maximum shear panels of the girders used in offshore and bridge constructions. Hence, this paper is devoted to the investigation of their effects on the strength and behaviour of hollow tubular flange plate girders (HTFPGs), which were previously suggested in literature to enhance the lateral–torsional, flexural and shear strengths of plate girders. The finite element (FE) programme ABAQUS is currently used to generate parametric studies after validating the models by using the available experimental results in literature. These parametric studies have emphasised on four main parameters; namely, the depth of the tubular flange, the relative web opening size ( d 0 / h w ), the web plate slenderness and the opening location. The eccentric openings are located at the corners of the tension and the compression diagonals of the maximum shear panels of the considered HTFPGs. The results show that the tubular flanges bear a considerable amount of shear even if the web openings are existed. Also, it is found that locating the openings, as possible, in the corners of the compression diagonals becomes an effective solution to reduce the shear loss associated with the presence of openings in the HTFPGs compared to those located at the tension diagonal corners. For cases of openings of different sizes in the tension corners as well as large openings in the compression corners, the existence of the opening is shown to modify the behaviour near the opening compared to the opposite side of each girder at which the web is solid. On the opposite, small openings ( d 0 / h w ≤ 0.30 ) in the compression corners are found to have a minor effect on the girder's deformed shape and stress contour. It is, finally, found that the shear design model should consider the sum of the contributions of the flanges and the webs of the HTFPGs with eccentric web openings to accurately predict their strengths. However, several new conclusions on the shear strength and behaviour of the HTFPGs with eccentric web openings are presented. Highlights: Shear behaviour of tubular flange plate girders (HTFPGs) with openings is examined. Corner openings in the panel of maximum shear were considered. 3-D finite element (FE) modelling using ABAQUS computer package has been employed. The design model of HTFPGs considers the contributions of the web and flanges.